Analisis Penilaian Kinerja Aparatur Sipil Negara Di Dinas Kebudayaan Dan Pariwisata Kabupaten Kuantan Singingi - Risvandi Risvandi; Rika Ramadhanti; Sarjan M; Melliofatria Melliofatria; Tria Anggraini; Nurmetri Nurmetri; Alya Imeldi Arizona (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
For the public sector (HR), the bureaucracy's major responsibility in providing services to the public must be supported by professional and competen ASN. The reason is that ASN influences the efficiency and effectiveness that occurs in government agencies both at the central and regional levels. To date, the quality of bureaucratic apparatus in providing public services in Indonesia continues to face various challenges. The public, as customers and users of these bureaucratic services, frequently complains about the quality and quantity of apparatus in carrying out their duties and functions. The research problem is formulated as follows How is the performance of State Civil Apparatus (ASN) at the Department of Culture and Tourism (DISBUDPAR) of Kuantan Singingi Regency. Study Objective To increase knowledge insight To know and analyze State Apparatus Civil (ASN) Performance at the Department of Culture and Tourism (DISBUDPAR) of Singingi Regency. The lack of ASN’s work quality can be seen from aspects of standard conformity.